Process performance maps for membrane-based CO2 separation using artificial neural networks. (January 2023) - Gasós, Antonio; Becattini, Viola; Brunetti, Adele; Barbieri, Giuseppe; Mazzotti, Marco
Abstract: Membrane-based gas separation processes are currently being implemented at different scales for several industrial applications. The optimal design of such processes, which is of key importance for their large-scale commercial deployment, has been extensively studied through parametric analyses and optimisation procedures. Nevertheless, the applicability of such design methodologies is generally limited by the large computational time and effort they require. In this work, surrogate models based on artificial neural networks are developed to circumvent the lengthy optimisation of a one-stage and two-stage cascade membrane-based gas separation process. In 200 ms, the surrogate model generates a Pareto front that describes the optimal trade-off between the process specific electricity consumption and productivity based on given input data, i.e., membrane material properties, feed composition and separation target. Whereas the surrogate model is applicable to any binary gas mixture, here its features are illustrated by creating process performance maps for post-combustion CO2 capture. Such maps provide valuable insights on: (i) attainable gas separation regions in term of CO2 recovery and CO2 purity, and (ii) the impact of membrane material, feed composition and separation target on the Pareto fronts and the optimal operating conditions. Highlights: Multi-objective optimisation of one- and two-stage membrane gas separation processes. Surrogate model based on artificial neural networks predicts optimisation outputs. Electricity-productivity Pareto optimal fronts for CO2 capture generated in 200 ms. Optimal membrane materials and operating conditions investigated via performance maps.